If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-1)=3x-4
We move all terms to the left:
3(x-1)-(3x-4)=0
We multiply parentheses
3x-(3x-4)-3=0
We get rid of parentheses
3x-3x+4-3=0
We add all the numbers together, and all the variables
1!=0
There is no solution for this equation
| 5x^2-4x-217=0 | | 3/5x+2=-11 | | 6-11n=15-2n | | 4t+20=4t+20 | | 7(2e−1)−3=6+6e7 | | -2(-4x+2)=4 | | -2+4r=10 | | 4/3(6x+9)4=x | | 3v-3=120 | | 4x2+20+9=0 | | |3x-2|=10 | | 4-3/4x=10 | | (3s-4)+(6+5)+s=47 | | A=9/4(h-63) | | 8n-15=5n-6 | | 31/5+2/5g-4/5(1-g)=2/5 | | /4x2+20+9=0 | | 4n-122=116 | | 5x/9-4=6 | | 6(20•7)-20=6x20 | | (1/x)=1.05 | | 7h+9=28 | | 2m+3=66 | | x^2=676-100 | | 3(-2+2x)=-6 | | 6z+13=55 | | -3(2x+2)=24 | | 0.3-1/5b=2.5b+5/2 | | 3m+5=66 | | x/5+5=x/4+4 | | 61/5+2/5g-4/5(1-g)=2/5 | | n/5-12=18 |